The Actors of Human Implantation: Gametes, Embryo, Endometrium - Gridelet, Virginie; Gaspard, Olivier; Polese, Barbara; Ruggeri, Philippe; Ravet, Stephanie; Munaut, Carine; Geenen, Vincent; Foidart, Jean-Michel; Lédée, Nathalie; d'Hauterive, Sophie Perrier (IntechOpen, 2012)
None